Effects of hearing impairment and hearing aid amplification on listening effort - a systematic review - Ohlenforst, Barbara; Zekveld, Adriana; Jansma, Elise; Wang, Yang; Naylor, Graham; Lorens, Artur; Lunner, Thomas; Kramer, Sophia (Lippincott, Williams & Wilkins, 2017)
Objectives: To undertake a systematic review of available evidence on the effect of hearing impairment and hearing-aid amplification on listening effort. Two research questions were addressed: Q1) does hearing impairment affect listening effort? and Q2) can hearing aid amplification affect listening effort during speech comprehension? Design: English language articles were identified through systematic searches in PubMed, EMBASE, Cinahl, the Cochrane Library, and PsycINFO from inception to August 2014. References of eligible studies were checked. The Population, Intervention, Control, Outcomes and Study design (PICOS) strategy was used to create inclusion criteria for relevance. It was not feasible to apply a meta-analysis of the results from comparable studies. For the articles identified as relevant, a quality rating, based on the 2011 Grading of Recommendations Assessment, Development and Evaluation (GRADE) Working Group guidelines, was carried out to judge the reliability and confidence of the estimated effects. Results: The primary search produced 7017 unique hits using the key-words: hearing aids OR hearing impairment AND listening effort OR perceptual effort OR ease of listening. Of these, 41 articles fulfilled the PICOS selection criteria of: experimental work on hearing impairment OR hearing aid technologies AND listening effort OR fatigue during speech perception. The methods applied in those articles were categorized into subjective, behavioral and physiological assessment of listening effort. For each study, the statistical analysis addressing research question Q1 and/or Q2 was extracted. In 7 articles more than one measure of listening effort was provided. Evidence relating to Q1 was provided by 21 articles that reported 41 relevant findings. Evidence relating to Q2 was provided by 27 articles that reported 56 relevant findings. The quality of evidence on both research questions (Q1 and Q2) was very low, according to the GRADE Working Group guidelines. We tested the statistical evidence across studies with non-parametric tests. The testing revealed only one consistent effect across studies, namely that listening effort was higher for hearing-impaired listeners compared to normal-hearing listeners (Q1) as measured by EEG measures. For all other studies the evidence across studies failed to reveal consistent effects on listening effort. Conclusion: In summary, we could only identify scientific evidence from physiological measurement methods, suggesting that hearing impairment increases listening effort during speech perception (Q1). There was no systematic finding across studies indicating that hearing-aid amplification decreases listening effort (Q2). In general, there were large differences in the study population, the control groups and conditions, and the outcome measures applied between the studies included in this review. The results of this review indicate that published listening effort studies lack consistency, lack standardization across studies, and have insufficient statistical power. The findings underline the need for a common conceptual framework for listening effort to address the current shortcomings.